Physical activity pattern in Iran: Findings from STEPS 2021 - Nejadghaderi, Seyed Aria; Ahmadi, Naser; Rashidi, Mohammad-Mahdi; Ghanbari, Ali; Noori, Maryam; Abbasi-Kangevari, Mohsen; Nasserinejad, Maryam; Rezaei, Negar; Yoosefi, Moein; Fattahi, Nima; Ghasemi, Erfan; Farzi, Yosef; et al. (Frontiers in Public Health, 2023)
Background Insufficient physical activity (IPA) is a significant risk factor for various non-communicable diseases. The Iran action plan is a 20% reduction in IPA. Therefore, we aimed to describe the age and sex pattern of physical activity domains, IPA, the intensity of physical activity, sedentary behavior, and their associates at Iran's national and provincial levels in 2021. Methods This study used the data of the STEPwise Approach to NCD Risk Factor Surveillance (STEPS) 2021 in Iran. The STEPS study used the Global Physical Activity Questionnaire (GPAQ) version two developed by WHO for the assessment of physical activity, which included work, transport, and recreational activities domains. We showed and compared demographic and clinical characteristics of participants between males and females, using t-test and Chi-square test. A logistic regression model adjusted for residential areas, years of schooling, wealth index, age, marital status, and occupation has also been implemented. The results were presented as percentages and 95% confidence intervals (CI). Results We included 27,874 participants with a mean (SD) age of 45.69 (15.91), among whom 12,479 (44.77%) were male. The mean prevalence of IPA for the whole population for all ages was 51.3% (50.62–51.98%). By sex, 41.93% (40.88–42.98%) and 57.87% (56.99–58.75%) of men and women had IPA, respectively. According to the physical activity domains, the age-standardized prevalence of no recreational activity was 79.40% (78.80–79.99%), no activity at work was 66.66% (65.99–67.32%), and no activity at transport was 49.40% (48.68–50.11%) for both sexes combined. Also, the overall age-standardized prevalence of sedentary behaviors was 50.82% (50.11–51.53%). Yazd province represented the highest prevalence of IPA (63.45%), while West Azerbaijan province represented the lowest prevalence (39.53%). Among both sexes, living in the urban area vs. rural area [adjusted OR: 1.44; (1.31–1.58)], married vs. single status [adjusted OR: 1.33; (1.16–1.53)], and wealth index of class 3 vs. class 1 [adjusted OR: 1.15; (1.01–1.30)] were significantly associated with a higher rate of IPA. Conclusion The prevalence of IPA was considerably high in Iran. To achieve the predefined goal of reducing IPA, the health system should prioritize increasing physical activity, especially in urban areas and among females.